Synthesis of gelatin‐based biodegradable hydrogel nanocomposite and their application as drug delivery agent - Bakravi, Asghar; Ahamadian, Yashar; Hashemi, Hamed; Namazi, Hassan (Advances in polymer technology, 2018)
In this work, gelatin was chemically cross‐linked using epichlorohydrin. Then, a series of gelatin‐based hydrogel nanocomposites containing CuO nanoparticles were prepared by immersion of gelatin hydrogel in CuCl2 solution with different concentrations. Gelatin was chosen, due to its cheapness, nontoxicity, and biocompatibility. The structure and morphology of hydrogel nanocomposites were characterized by a number of techniques such as FT‐IR, XRD, energy dispersive X‐ray spectroscopy, and scanning electron microscopy. Then, swelling behavior of synthesized hydrogel nanocomposites in distilled water and different saline solutions was investigated. Their sensitivity to pH, biodegradability, and gel content was determined. Moreover, the water uptake and shrinking kinetics of hydrogel nanocomposites were evaluated. Finally, they were used as drug delivery agent, and the different concentrations effect of CuO nanoparticles present within the hydrogel nanocomposites compared with neat hydrogel on mentioned tests was studied.